Forest policies in Malawi, Mozambique, Tanzania and Zimbabwe - Kowero, G.S.; Kaoneka, A.S.; Nhantumbo, I.; Gondo, P.; Jumbe, C.B.L. (Kluwer Academic Publishers, 2001)
Many countries in eastern and southern Africa have lost significant natural forest resources. Initially the pace was gradual, but it has accelerated very much in the recent past. Some of the efforts made to contain the situation include revising past policies to improve forestry development and conservation. This paper traces the evolution of such policies together with corresponding implementation mechanisms in Malawi, Mozambique, Tanzania and Zimbabwe. Although broad policy statements on involving local communities in forestry have existed in some countries for several decades, adequate resources have not been committed for their effective operationalisation. Generally, the forestry sector in southern Africa has lagged behind other sectors in revising its policies to adequately reflect political and socio-economic changes. Political and socio-economic policies appear to have taken precedence over forest sector policies, with far reaching consequences for the sector. However, current forest policies are more comprehensive in terms of stakeholders considered and issues addressed.